Synthesis of 5-Aminosalicylic Acid using Kolbe-Schmidt Reaction Under Supercritical Conditions - Lu, Hailiang; Liu, Junqi; Xing, Cunzhang; Tan, Mingchen; Gao, Fei (Asian Journal of Chemistry, 2011)
5-Aminosalicylic acid is one of the preferred drugs in clinical treatment of inflammatory bowel disease, so it has important significance to investigate the process of its preparation. In this work, 5-aminosalicylic acid was synthesized by Kolbe-Schmidt reaction under supercritical conditions. Supercritical CO2 serves as both reactant and reaction medium in the reaction. The effects of various conditions, such as pressure, temperature, reaction time and stir speed, on the yield of 5-aminosalicylic acid were investigated. As the supercritical CO2 has high diffusion coefficient, high solubility, high mass transfer efficiency and effective heat transfer capacity, the reaction can be carried out in a homogenizing situation. The experimental results show that more than 90.5 % of the yield of 5-aminosalicylic acid can be obtained under the optimal reaction parameters such as pressure (9.0 MPa), temperature (140 ºC), reaction time (2.5 h) and stir speed (300 rpm). The results indicate that, in supercritical state, Kolbe-Schmidt reaction can be carried out with high speed at much lower temperature compared to that of the traditional technology and the product quality and production efficiency is also enhanced.